Morphological variation of hairs in Malva alcea L. (Malvaceae) - Celka, Zbigniew; Szkudlarz, Piotr; Biereżnoj, Urszula (Biodiversity: Research and Conservation, 2006)
Hairs are one of the key taxonomic features in the Malva alcea complex. The paper presents preliminary results of research on the morphology and variation of hairs in Malva alcea from different geographic regions of Poland. In the studied populations several types of trichomes were disitinguished, including simple ones (unibranched), bifurcate (2-branched) and stellate (multibranched, multicellular). Stellate hairs vary in number of branches from 3 to 10. However, in all types of trichomes (simple, bifurcate and stellate) each branch is composed exclusively of a single unbranched cell.